2020
DOI: 10.1007/s12630-020-01570-2
|View full text |Cite
|
Sign up to set email alerts
|

Video Modeling and Video Feedback to Reduce Time to Perform Intravenous Cannulation in Medical Students: A Randomized-Controlled Mixed-Methods Study

Abstract: Purpose Combined video modeling (VM) and video feedback (VF) may be more beneficial than traditional feedback when teaching procedural skills. This study examined whether repeated VM and VF compared with VM alone reduced the time required for medical students to perform peripheral intravenous (IV) cannulation. Methods Twenty-five novice medical students were randomly assigned to groups in a one-way blinded embedded mixed-methods study to perform IV cannulation.Participants received standardized instruction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…The quality of our in-task, concurrent feedback may have overshadowed any positive effect immersive VM could have had on the scoring. This has been recently studied in novice medical students [24], wherein early procedural learning benefitted from VM, but in later procedural interventions students subjectively benefitted more from concurrent feedback. Secondly, we identified that the cognitive load remained higher in the immersive VM group, which may have adversely affected performance.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of our in-task, concurrent feedback may have overshadowed any positive effect immersive VM could have had on the scoring. This has been recently studied in novice medical students [24], wherein early procedural learning benefitted from VM, but in later procedural interventions students subjectively benefitted more from concurrent feedback. Secondly, we identified that the cognitive load remained higher in the immersive VM group, which may have adversely affected performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that training efficiency by video feedback is superior to that by the traditional method in the fields of regional anesthesia and intravenous cannulation. 1,2 For assessing direct laryngoscopic view, the use of Google Glass (Google) was reported by Spencer et al 3 However, Google Glass is not appropriate for evaluating overall airway management because the view it provides is limited to the view of the person wearing it. Therefore, as a part of our quality improvement project, we decided to use GoPro (GoPro, Inc.,) for video feedback in pediatric airway management.…”
Section: The Use Of Gopro For Video Feedback In Training For Pediatric Airway Managementmentioning
confidence: 99%
“…There are only three single‐subject design studies (Dowrick & Dove, 1980; Quinn et al, 2020; Scott et al, 1998) evaluating VM alone for teaching sports skills for individual athletes. Similar to the sports literature, VM is often provided within a treatment package in other fields, such as teaching skills to individuals with autism spectrum disorder (McCoy & Hermansen, 2007; Park et al, 2019; Syriopoulou‐Delli & Sarri, 2021); training parents, educators, and human service staff to implement procedures or teach others (Gerencser et al, 2020; Marano et al, 2020) and training medical practitioners to perform medical procedures (Jamshidi et al, 2009; Yu et al, 2020). Researchers have suggested that VM alone should be assessed before adding other components to an intervention (e.g., Park et al, 2019) and described the advantages of minimizing trainer presence when teaching skills (e.g., Ericsson, 2014; Marano et al, 2020).…”
mentioning
confidence: 99%
“…Researchers in other fields have asserted that these independent opportunities are highly desirable for teaching medical procedures (e.g., Ericsson, 2014; Mota et al, 2018) and training staff (e.g., Gerencser et al, 2020; Marano et al, 2020). Medical practitioners receiving VM training have described the chance to have independent multiple viewings of a video as beneficial for thoroughly learning the skill and noticing new details (Yu et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation